The Meaning of Accounting: Exploring the Experiences of Local Business Actors (Case Study of Traditional Coffee Shop) - Nadila Nadila; Anastasia Gloria Panggeso; Darwis Said (Transpublika Publisher, 2025)
MSMEs are key players in the economy of Indonesia, but they often encounter difficulties in managing their finances, especially when it comes to creating accurate financial documents that adhere to accounting regulations. In regions such as North Kolaka, which are remote, these challenges are further exacerbated by the lack of access to formal accounting education and resources. This study aims to explore the experiences of Micro, Small, and Medium Enterprises (MSMEs) in North Kolaka, especially Warkop Bunda, in managing accounting and finance. Using a qualitative descriptive approach, this study analyzes simple financial recording practices and the meaning of accounting for business actors. The results show that although business owners rely on practical manual recording, they face significant obstacles, such as limited knowledge and resources to implement formal accounting. Financial recording functions more as a cash flow control tool and reflects social responsibility towards family and society. These findings highlight the need for accounting education and training that is appropriate to local needs, as well as a simpler accounting system to improve the efficiency of financial management. Hence, this study provides new insights for the development of policies and mentoring programs for MSMEs in the region.